Medication reconciliation of patients with hip fracture by clinical pharmacists - Gjerde, Anne Marie (Eur J Hosp Pharm, 2016)
OBJECTIVE: Medication reconciliation is a strategy for reducing medication discrepancies and improving patient safety. Transitions through different levels of care contribute to medication discrepancies caused by lack of communication. In October 2011, St Olav's Hospital initiated a fast-track model for patients with hip fractures, where clinical pharmacists (CPs) are a part of a multidisciplinary team. The purpose of this study was to examine discrepancies discovered in medication lists by CPs at the orthopaedic ward and consider their clinical relevance. METHOD: This prospective study was conducted at an orthopaedic ward at St Olav's Hospital in the period October 2011–August 2012. Medication reconciliation by CPs was done for all patients with a hip fracture using a systematic method. Information was obtained by the CP by interview with the patient and additional sources, for example, medication list from general practitioner and nursing home. An independent expert group consisting of a geriatrician, an orthopaedist and a CP considered level of clinical relevance of the discrepancies found in the collected data. RESULTS: A total of 410 discrepancies were registered for all 317 patients, Discrepancies were found in 159 (50%) patients with an average of 2.6 per patient affected. Of the total amount of discrepancies, the expert group evaluated 68% and 19% as potentially moderate and severe, respectively, if they were unattended during hospitalisation and after discharge. CONCLUSIONS: By using CPs in medication reconciliation at orthopaedic wards, discrepancies that can lead to serious discomfort or clinical deterioration of patients can be avoided.